Amazonian Moisture Recycling Revisited Using WRF With Water Vapor Tracers. Issue 4 (17th February 2022) - Dominguez, F.; Eiras‐Barca, J.; Yang, Z.; Bock, D.; Nieto, R.; Gimeno, L.
Abstract: Previous studies have estimated that 25%–35% of Amazonian precipitation comes from evapotranspiration (ET) within the basin. However, due to simplifying assumptions of traditional models, these studies primarily focus on large spatial and temporal scales. This study is the first to analyze the moisture of Amazonian origin at the annual to daily timescale in four different subregions of the Amazon. We analyze the sources, sinks and stores of moisture that originates as Amazonian ET. To do this, we use the Weather Research and Forecast (WRF) regional meteorological model with the added capability of water vapor tracers to track this moisture. Moisture of Amazonian origin shows strong annual and semi‐annual signals, with contrasting behavior between the northern and southern parts of the basin. The tracers reveal a strong diurnal cycle of Amazonian water vapor which had not been previously reported. This signal is related to the diurnal cycle of ET, convective precipitation and advected moisture. ET's contribution to atmospheric moisture increases from early morning into the afternoon. Some of this moisture is rained out through convective storms in the early evening. Later in the night and following morning, strong winds associated with the South American Low Level Jet advect moisture downwind. The beating pattern becomes apparent when visualizing the Amazonian water vapor as an animation. Plain Language Summary: Evaporation from soil and transpiration from plants within the Amazon contribute to approximately one third of the precipitation that falls within the basin in a process known as "precipitation recycling." This estimate represents an average over the basin and over many years. In this work we use numerical water tracers within an atmospheric model to quantify precipitation recycling at higher spatial and temporal resolution than previous studies. The tracers allow us to follow the water from the time it evaporates from the land until it falls as precipitation. Our work reveals cycles in water vapor and precipitation of Amazonian origin that had not been previously studied. In particular, the daily timescale shows how evaporation and transpiration increase from early morning into the afternoon and contribute to the accumulation of Amazonian water vapor in the atmosphere. Some of this moisture is rained out in the early evening in convective storms, while later in the night and morning strong winds transport moisture away from the basin. The beating pattern becomes apparent when visualizing the Amazonian water vapor as an animation. Key Points: 30% of Amazonian precipitation comes from local evapotranspiration. Recycled precipitation increases from east to west Amazonian moisture shows a strong annual and semi‐annual signal with contrasting behavior in the northern and southern parts of the basin A strong diurnal cycle of Amazonian water vapor is a result of the diurnal cycle of evapotranspiration, precipitation and vapor flux